1996
DOI: 10.1083/jcb.135.1.191
|View full text |Cite
|
Sign up to set email alerts
|

Local perinuclear calcium signals associated with mitosis-entry in early sea urchin embryos.

Abstract: Abstract. Using calcium-sensitive dyes together with their dextran conjugates and confocal microscopy, we have looked for evidence of localized calcium signaling in the region of the nucleus before entry into mitosis, using the sea urchin egg first mitotic cell cycle as a model. Global calcium transients that appear to originate from the nuclear area are often observed just before nuclear envelope breakdown (NEB). In the absence of global increases in calcium, confocal microscopy using Calcium Green-1 dextran … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 66 publications
8
75
0
Order By: Relevance
“…This idea was supported by early reports that [Ca 2+ ] is elevated at spindle poles before anaphase in PTK and endosperm cells (Keith et al, 1985;Ratan et al, 1986). More recently, using confocal imaging and ratiometric Ca 2+ indicators, localized Ca 2+ increases were detected in the perinuclear region just before NEBD in sea-urchin embryos (Wilding et al, 1996). Consistent with the ability to generate local Ca 2+ signals is the observation that, shortly before NEBD, the endoplasmic reticulum aggregates around the nucleus (Terasaki, 2000).…”
Section: Casupporting
confidence: 70%
See 3 more Smart Citations
“…This idea was supported by early reports that [Ca 2+ ] is elevated at spindle poles before anaphase in PTK and endosperm cells (Keith et al, 1985;Ratan et al, 1986). More recently, using confocal imaging and ratiometric Ca 2+ indicators, localized Ca 2+ increases were detected in the perinuclear region just before NEBD in sea-urchin embryos (Wilding et al, 1996). Consistent with the ability to generate local Ca 2+ signals is the observation that, shortly before NEBD, the endoplasmic reticulum aggregates around the nucleus (Terasaki, 2000).…”
Section: Casupporting
confidence: 70%
“…This was the case in fertilized embryos that generate Ca 2+ transients and in parthenogenetic embryos that do not (Tombes et al, 1992;Kono et al, 1996) (present study). Similarly, in sea-urchin embryos and fibroblasts, BAPTA inhibits mitosis despite the absence of detectable Ca 2+ transients in many cases (Kao et al, 1990;Wilding et al, 1996). These inconsistencies could be reconciled after it was found that local perinuclear [Ca 2+ ] increases, which were not detectable using epifluorescence microscopy, were detectable using ratiometric confocal microscopy in sea-urchin embryos (Wilding et al, 1996).…”
Section: Fig 8 Mitotic Camentioning
confidence: 88%
See 2 more Smart Citations
“…Microinjection of calcium or InsP 3 induces NEB precociously (Steinhardt & Alderton 1988;Twigg et al 1988) and calcium chelators block NEB reversibly (Wilding et al 1996). NEB in starfish embryos is also preceded by a calcium spike and blocked by heparin injection (Stricker 1995).…”
Section: Calcium and The Early Embryonic Cell Cyclesmentioning
confidence: 99%